Monitoring and Evaluation form Project Implementation in Strategic of Rajabhat University for Develop Local of Buriram Rajabhat University in Fiscal Year 2022 - Kultanan, Phatchanee; Buranaphansak, Ketsuda; Chanwongduen, Chatsaphon (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
The purpose of this research was to study the body of knowledge, evaluation and study the satisfaction with the project implementation in strategic of Rajabhat University for develop local of Buriram Rajabhat University in fiscal year 2022. The target group for the evaluation of the project implementation consisted of 6 experts. The sample group for the satisfaction of the project implementation were students, teachers, teachers, school administrators, community leaders. and villagers participating in 22 projects of 220 people. The research instruments were the project assessment form and the project satisfaction questionnaire. The statistics used in the research were percentage, mean, standard deviation and content analysis. The research finding revealed as follows: 1. there are 22 projects, all of which cover the upstream phase, midstream and downstream to develop local and educational. There are issues related to waste recycling, social engineers , the use of technology for adding products’ value, control and prevention of the new coronavirus disease 2019, community water management, art education center, short course, classroom research, coding program, the dynamics book from Geogebra program, a learning management plan, measuring and evaluating real-world conditions and performance, English language development, reading, writing, critical thinking and the development of music teachers; 2. the project overall and individual assessment results at the highest level of 4 projects.